Social Motivation Across Multiple Measures: Caregiver‐Report of Children with Autism Spectrum Disorder. Issue 2 (14th September 2020) - Neuhaus, Emily; Bernier, Raphael A.; Webb, Sara J.
Abstract : Social motivation is a foundational construct with regard to the etiology, neurobiology, and phenotype of autism spectrum disorder (ASD). Multiple theories suggest that early emerging alterations to social motivation underlie a developmental cascade of social and communication deficits across the lifespan. Despite this significance, methods to measure social motivation vary widely, with little data to date as to how different measures might compare. In this study, we explore three existing caregiver‐report measures that have been proposed to quantify social motivation among school‐age children with ASD ( n = 18; all male) and without ASD ( n = 36; 50% female), with the broad goal of characterizing social motivation across measures and specific aims of investigating (a) diagnostic and sex differences in social motivation, (b) correspondence between measures, and (c) relationships between social motivation and broader social outcomes. Across all three measures, individuals with ASD had lower social motivation by caregiver‐report. However, they did display individual differences in the degree of social motivation reported. There were no differences in social motivation between males and females without ASD on any of the three measures. For the full sample, measures of social motivation correlated with one another as anticipated, and stronger social motivation was associated with stronger social skills and fewer social difficulties. Our data suggest that social motivation among children with ASD may be best conceptualized as an individual difference that is diminished on average relative to peers but which varies among children and adolescents with ASD, rather than as an absolute absence or uniform deficit. Lay Summary: Several theories suggest that children with autism spectrum disorder (ASD) experience less social motivation than their peers without ASD, contributing to difficulties in social skills. Based on multiple caregiver‐report questionnaires, social motivation was reduced on average for school‐age children with ASD but also varied among children with ASD. Stronger social motivation was related to stronger social skills and fewer social problems. Future work should include more girls with ASD, consider social motivation across age groups, and include first‐hand perspectives from people with ASD.